2005
DOI: 10.1111/j.1464-410x.2005.05510.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical radical retropubic prostatectomy: ‘curtain dissection’ of the neurovascular bundle

Abstract: OBJECTIVE To investigate the topographical relationship of the cavernosal nerves (CNs) to seminal vesicles, prostate, rhabdosphincter and urethra during the development of the prostate, and to use the resulting morphological data to modify the surgical technique of nerve‐sparing radical prostatectomy. MATERIALS AND METHODS The study included 29 male fetuses (gestational age 9–37 weeks) and eight adult specimens assessed anatomically and histologically. Using the plastination technique and anatomical dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(90 citation statements)
references
References 23 publications
2
82
0
6
Order By: Relevance
“…Одним из главных аспектов пробле-мы удержания мочи является понимание анатомии уретрального сфинктера, наружный мышечный слой которого представлен поперечно-полосатыми волок-нами, наиболее выраженными в вентральном и вентро-латеральных отделах. В литературе по отношению к данной структуре часто используют термин «попе-речно-полосатый сфинктер» («рабдосфинктер») [11][12][13][14]. Внутренний мышечный слой уретрального сфинктера образован гладкими волокнами, смешанно ориентированными в 2 направлениях: циркулярном и продольном [15,16].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
See 3 more Smart Citations
“…Одним из главных аспектов пробле-мы удержания мочи является понимание анатомии уретрального сфинктера, наружный мышечный слой которого представлен поперечно-полосатыми волок-нами, наиболее выраженными в вентральном и вентро-латеральных отделах. В литературе по отношению к данной структуре часто используют термин «попе-речно-полосатый сфинктер» («рабдосфинктер») [11][12][13][14]. Внутренний мышечный слой уретрального сфинктера образован гладкими волокнами, смешанно ориентированными в 2 направлениях: циркулярном и продольном [15,16].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…В 1-ю группу включены 55 мужчин, которым на этапе наложения уретроцистоанастомоза швы по передней полуокруж-ности уретры на 1 и 11 ч условного циферблата выпол-няли с захватом венозного дорсального комплекса ОНКОУРОЛОГИЯ 4'2017 ТОМ 13 CANCER UROLOGY 4'2017 VOL. 13 Диагностика и лечение опухолей мочеполовой системы. Рак предстательной железы и пубопростатических связок.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
See 2 more Smart Citations
“…[1][2][3][4] The concept of the neurovascular bundle (NVB) was advocated by Walsh and Donker, 1 whereas Costello et al 2 reported that most of the nerves included in NVB originally descend posterior to the seminal vesicle, converging at the midprostatic level only to diverge once again as they approach the prostatic apex. Although the nerve-sparing procedure based on anatomic research is widely performed to restore erectile function after radical prostatectomy, postoperative potency rates reported by other institutes varied with age, preoperative sexual function, surgeon and postoperative period.…”
Section: Introductionmentioning
confidence: 99%